A facile dynamic crosslinked healable poly(oxime-urethane) elastomer with high elastic recovery and recyclability. Issue 37 (12th September 2018) - Fu, Daihua; Pu, Wuli; Wang, Zhanhua; Lu, Xili; Sun, Shaojie; Yu, Changjiang; Xia, Hesheng
Abstract : Catalyst-free and colorless transparent healable and recyclable poly(oxime-urethane) elastomers were developed with scaling-up capability using low-cost and commercially available compounds. Abstract : Endowing thermoset polymer materials with self-healing and recyclable properties by incorporating dynamic bonds into the polymer networks is of vital realistic significance. However, such materials are still limited because of the difficult synthetic process and expensive dynamic monomers or environment-unfriendly catalysts. Herein, catalyst-free and colorless transparent healable and recyclable poly(oxime-urethane) elastomers based on dynamic oxime–carbamate bonds were developed with scaling-up capability using low-cost and commercially available compounds. These materials display remarkable comprehensive properties and relatively low relaxation activation energy (∼29.7 kcal mol −1 ) which results in excellent healable and recyclable performance. The poly(oxime-urethane) with a crosslink density ν of ∼0.2 mmol cm −3 possesses a tensile strength of ∼13.5 MPa, a breaking strain of ∼812%, toughness up to ∼40 MJ m −3, an excellent elastic recovery of ∼90% and an average optical transmittance of ∼86% in the visible range. This material can be completely healed at 110 °C in 0.5 h. In situ structural characterizations revealed that the dynamic properties originate from the reversibility of oxime–carbamate bonds and hydrogen bonds.